Effect of Mercury Stress on the Growth and Lipid Content of Euglena sp. and Echinodorus palaefolius - Wisnu Eka Wardana; Dea Hastaning Tantri; Marshanda Nur Roosyana Afifah; Hasna Nur Aini; Dwi Umi Siswanti; Khusnul Qonita Maghfiroh; Tia Erfianti; Ria Amelia; Dedy Kurnianto; Eko Agus Suyono (UIN Sunan Gunung Djati Bandung, 2023)
One way to reduce the adverse effects of the heavy metals mercury in the aquatic environment are using organisms to break down or convert toxic substances into non-toxic forms, either by phytore- mediation or phycoremediation. This research aimed to analyze the growth and lipid content of Euglena sp. after mercury exposure. This research also aimed to analyze the growth of E. palaefolius which is associated with Euglena sp. In this study, the bioremediation ability of Euglena sp. and Echinodorus palaefolius through treatment with mercury concentrations of 5 ppm, 10 ppm, 15 ppm, and 20 ppm, as well as association and non-association treatments. The parameters are the growth of Euglena sp. and the association between Euglena sp. andE. palaefolius measurement and lipid content. The result of the growth of Euglena sp. experienced a significant increase. Lipid content in Euglena sp. was also seen high at 10 ppm mercury concentration. In E. palaefolius, the ability to adsorb heavy metals was also shown by the large diameter of the stems and also the plant growth which has optimal growth in the treatment of 10 ppm mercury stress.